Exports, foreign direct investments and productivity: Are services firms different? - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
This paper contributes to the literature on international firm activities and firm performance by providing the first evidence on the link of productivity and both exports and foreign direct investment (fdi) in services firms from a highly developed country. It uses unique new data from Germany - one of the leading actors on the world market for services - that merge information from regular surveys and from a one-time special purpose survey performed by the Statistical Offices. Descriptive statistics, parametric and non-parametric statistical tests and regression analyses (with and without explicitly taking differences along the conditional productivity distribution and firms with extreme values, or outliers, into account) indicate that the productivity pecking order found in numerous studies using data for firms from manufacturing industries - where the firms with the highest productivity engage in fdi while the least productive firms serve the home market only and the productivity of exporting firms is in between - does not exist among firms from services industries. In line with the theoretical model and the empirical results for software firms from India provided by Bhattacharya, Patnaik and Shah (2010) there is evidence that firms with fdi are less productive than firms that export.
Keywords: F14; F21; 330; exports; foreign direct investments; productivity; services firms; Unternehmensdienstleistung; Export; Internationaler Dienstleistungsverkehr; Direktinvestition; Unternehmensentwicklung; Produktivität; Deutschland